1981
DOI: 10.1104/pp.68.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Positional Specificity and Fatty Acid Selectivity of Purified sn-Glycerol 3-Phosphate Acyltransferases from Chloroplasts

Abstract: Soluble acyl-CoAsn-glycerol 3-phosphate acyltransferases (EC 23.1.15) which are localized in chloroplasts were purified from leaves of Pisum sativum and Spinacia oke.aca and obtained free from interfering activities. The purification raised the specific activities by factors of about 1,000 for pea and 200 for spinach preparations. In pea chloroplasts, acyltransferase activity occurs in two soluble forms with apparent isoelectric points of 6.3 and 6.6. For both forms, the same molecular weight of about 42,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 14 publications
4
52
0
2
Order By: Relevance
“…We studied the response of the HaPLSB enzyme to pH using palmitoyl-ACP as an acyl donor, observing maximum HaPLSB activity at pH 6.9 that decreased significantly up to pH 8.0. This pH curve ( Figure 6C) is similar to that reported for the pea chloroplast GPAT (Bertrams and Heinz, 1981), for which the optimal pH value is 7.4. A recent study reported that the activity of the plastidial GPAT from eight different plant species at pH 7.4 is lower than at pH 8.0 (Zhu et al, 2009), showing that plastidial GPAT activity responds to pH changes.…”
Section: Effect Of Ph On Haplsb Activitysupporting
confidence: 73%
“…We studied the response of the HaPLSB enzyme to pH using palmitoyl-ACP as an acyl donor, observing maximum HaPLSB activity at pH 6.9 that decreased significantly up to pH 8.0. This pH curve ( Figure 6C) is similar to that reported for the pea chloroplast GPAT (Bertrams and Heinz, 1981), for which the optimal pH value is 7.4. A recent study reported that the activity of the plastidial GPAT from eight different plant species at pH 7.4 is lower than at pH 8.0 (Zhu et al, 2009), showing that plastidial GPAT activity responds to pH changes.…”
Section: Effect Of Ph On Haplsb Activitysupporting
confidence: 73%
“…Under the conditions described previously (20), total acetate incorporation into lipid was linear up to I h after which the incorporation tapered off and by 3 …”
Section: Resultsmentioning
confidence: 99%
“…Immediately after GPAT assay, 0.1 M borate buffer (pH 7.5, 1 mL) and 0.1 M Tris·HCl (pH 7.5, 1 mL) were added. Dephosphorylation (17) was started by adding 1 μL of Escherichia coli alkaline phosphatase (0.25 unit) and continued for 30 min at room temperature. Products were extracted by diethyl ether, and MAGs were separated by borate-TLC.…”
Section: Transformation and Expression Of Gpats And Their Vector Contmentioning
confidence: 99%